1997
DOI: 10.1111/j.1471-6712.1997.tb00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Needs as Expressed by Women after Breast Cancer Surgery in the Setting of a Short Hospital Stay

Abstract: The aim of this study was to describe needs as expressed by a group of women after surgery for breast cancer in the setting of a short hospital stay. Ten days after surgery, 97 women answered an open-ended question about their perception of the care given. A content analysis inspired by the method of Grounded Theory was used. Satisfaction with the personal treatment and feelings of abandonment were identified as the two main themes. Expressed needs (n = 113) were classified in five categories: Trust, Informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 26 publications
3
27
0
Order By: Relevance
“…For instance, cancer patients often find themselves confronting complex information about their disease and must cope with both the physical and psychological toll of their illness (Boman, Andersson, & Bjorvell, 1997;Breau, McGrath, & Norman, 2003;Degner et al, 1997). For these reasons the Internet holds promise, as it can serve as a communication medium for individuals sharing information and emotional support about cancer, empowering cancer information consumers to act as competent social actors, and allowing them to become increasingly involved in their own health care (Ziebland, 2004;Ziebland et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, cancer patients often find themselves confronting complex information about their disease and must cope with both the physical and psychological toll of their illness (Boman, Andersson, & Bjorvell, 1997;Breau, McGrath, & Norman, 2003;Degner et al, 1997). For these reasons the Internet holds promise, as it can serve as a communication medium for individuals sharing information and emotional support about cancer, empowering cancer information consumers to act as competent social actors, and allowing them to become increasingly involved in their own health care (Ziebland, 2004;Ziebland et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A study in Sweden [5] has shown a lack of information about postoperative rehabilitation, particularly exercise after operation, and how much to lift and work using the arm on the operated side. In a study in the USA, more than half (60%) of breast cancer survivors reported that their physicians did not mention exercise to them as part of their rehabilitation [45].…”
mentioning
confidence: 98%
“…Several authors suggest that more nurse time in a patient room is associated with better patient outcomes (Aiken, Clarke, Sloane, Sochalski, & Silber, 2002;Anderson, 2007;Kovner, Jones, Zhan, Gergen, & Basu, 2002;Needleman, Buerhaus, Mattke, Stewart, & Zelevinsky, 2002;Westbrook, Duffield, Li, & Creswick, 2011). Indeed, patients themselves desire to have more time with their nurse (Boman, Andersson, & Bj€ orvell, 1997).…”
Section: Nurse Presence In Patient Roomsmentioning
confidence: 94%